If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + 6(6 + 6m) = 116 8 + (6 * 6 + 6m * 6) = 116 8 + (36 + 36m) = 116 Combine like terms: 8 + 36 = 44 44 + 36m = 116 Solving 44 + 36m = 116 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-44' to each side of the equation. 44 + -44 + 36m = 116 + -44 Combine like terms: 44 + -44 = 0 0 + 36m = 116 + -44 36m = 116 + -44 Combine like terms: 116 + -44 = 72 36m = 72 Divide each side by '36'. m = 2 Simplifying m = 2
| 3h-1=5 | | 18-3n=4n+11 | | 13+8m=7m+14 | | w+15=2 | | 1-7y=2y-14 | | (2x)(x+4)=0 | | 5t+4r+9=0 | | 9+3.5f=11-0.5g | | 36+2y=-4y | | 5x+9-3x=0 | | X^2-4x-k+4=0 | | x+73=4961 | | 29-y=37 | | 5x+9=11x-27 | | (x)(4x+5)=520 | | 2y=-3x+29 | | -7x+9=19-3x | | -2y-3y+9=4-3-y | | 600=300+10c | | X^2-12x+49=22 | | 13y+2=9y+22 | | 97b=2037 | | 14x-9x=7 | | 11n^2=5n^2 | | 16b=128 | | 600=5s+400 | | x-.16x=543.90 | | 11x-4=117 | | x-.16=543.90 | | 600=175+10c | | 4n-3=4n-3 | | 4y^2+36y+72=0 |